The relationship between physical activity and mental health of middle school students: the chain mediating role of negative emotions and self-efficacy - Yan, Hao-Ming; Huang, Ping; Chen, Rui; Wang, Yi-Cheng (Frontiers in Psychology, 2024)
Objective To explore the relationship between mental health and physical activity (PA) in middle school students, and examining the roles of negative emotions and self-efficacy in the relationship. Methods Data from 1,134 Chinese middle school students (50.2% females, 49.8% males; Mage = 15.18, SDage = 2.00) were collected using the Physical Activity Rating Scale (PARS-3), Positive and Negative Affect Scale (PANAS), General Self-Efficacy Scale (GSES), and Middle School Student Mental Health Scale (MSSMHS). Results (1) There is a significant positive correlation between PA and mental health (r = 0.16, p < 0.01), and the direct path of PA on mental health is significant (t = 2.101, p < 0.01). (2) PA negatively predicts negative emotions (r = −0.12, p < 0.01), and is significantly positively correlated with self-efficacy (r = 0.24, p < 0.01). Negative emotions negatively predict self-efficacy (r = −0.23, p < 0.01) and mental health (r = −0.67, p < 0.01). Self-efficacy positively predicts mental health (r = 0.30, p < 0.01). (3) Negative emotions and self-efficacy play a significant mediating role between PA and mental health. The mediating effect includes three paths: PA → negative emotion → mental health (effect value: 0.130); PA → self-efficacy → mental health (effect size: 0.052); PA → negative emotions → self-efficacy → mental health (effect size: 0.006). Conclusion PA among middle school students can indirectly affect mental health through negative emotions and self-efficacy. Middle school students should be encouraged to participate in PA to reduce their negative emotions and increase their self-efficacy, thus improving their mental health.